1998
DOI: 10.1002/hep.510280430
|View full text |Cite
|
Sign up to set email alerts
|

10-year follow-up after interferon-α therapy for chronic hepatitis C

Abstract: Sustained responses to interferon-␣ occur in 10% to 25% of patients with chronic hepatitis C, but the long-term outcome is not well defined. We evaluated the long-term clinical, histological, and virological outcomes of 10 patients with chronic hepatitis C who were treated between 1984 and 1987 with interferon-␣-2b for 52 ؎ 6 weeks (total doses of 492 ؎ 116 MU). Before therapy, all 10 had hepatitis C virus (HCV) RNA, elevations of serum aminotransferases, and chronic hepatitis with fibrosis on liver biopsy. Cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
149
0
6

Year Published

2000
2000
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(165 citation statements)
references
References 38 publications
10
149
0
6
Order By: Relevance
“…Termination of the necro-inflammatory reaction after clearance of the underlying etiological factor(s) might result in improvement of liver fibrosis (1,(9)(10)(11)(12)(13)(14). In particular, IFN treatment has been clinically used for infected patients for over ten years in Japan.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Termination of the necro-inflammatory reaction after clearance of the underlying etiological factor(s) might result in improvement of liver fibrosis (1,(9)(10)(11)(12)(13)(14). In particular, IFN treatment has been clinically used for infected patients for over ten years in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies indicated that liver fibrosis is a reversible process despite the potential progression to liver cirrhosis (1)(2)(3)(4)(5)(6). Clinically, we have encountered several patients who showed histopathological improvement of liver fibrosis during long-term follow-up after interferon (IFN) therapy for HCV infection.…”
Section: Introductionmentioning
confidence: 99%
“…Long-term follow-up studies showed that the vast majority of the sustained virologic responders are probably cured from HCV infection. [44][45][46] HCV resistance is defined as HCV RNA persistence in serum after therapy. The incidence of HCV resistance to IFN-based therapies varies according to the administered regimen.…”
Section: Definitions: Incidence and Patterns Of Hcv Resistance To Antmentioning
confidence: 99%
“…Currently, anti-viral therapy for chronic hepatitis C is successful in approximately 50% of infected patients, resulting in clearance of HCV-RNA from serum, normalization of liver function tests and improvement of liver histology. 11,12 This standard treatment is the combination of pegylated-interferon (1.5 lg/kg subcutaneously once weekly) and ribavirin (800-1200 mg/p.o./day) for 6-12 months. The aim of this work was to study the response to anti-viral treatment in patients with occult HCV infection in order to assess the possible pathogenic effect of occult HCV.…”
Section: Introductionmentioning
confidence: 99%